2015
DOI: 10.3892/ol.2015.3220
|View full text |Cite
|
Sign up to set email alerts
|

Hispolon inhibits TPA-induced invasion by reducing MMP-9 expression through the NF-κB signaling pathway in MDA-MB-231 human breast cancer cells

Abstract: Abstract. Hispolon has been demonstrated to possess analgesic, anti-inflammatory and anticancer activities. However, whether hispolon prevents the invasion of breast carcinoma cells and the underlying mechanisms of its action remain unknown. In the present study, various assays, including a matrigel-based Transwell invasion assay and electrophoretic mobility shift assay, were used to investigate the anti-invasion effect of hispolon and explore its mechanism of action. The results revealed that hispolon inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Moreover, numerous studies have shown the antiproliferation activity of hispolon in many types of human cancers. Our previous research showed hispolon could inhibit TPA-induced migration and invasion of MDA-MB-231 cells by reducing MMP-9 secretion and expression, mainly through the NF-κB signaling pathway (49). In the present study, we confirmed that hispolon can inhibit the migration of MCF-7, breast cancer cells by a completely different mechanism.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, numerous studies have shown the antiproliferation activity of hispolon in many types of human cancers. Our previous research showed hispolon could inhibit TPA-induced migration and invasion of MDA-MB-231 cells by reducing MMP-9 secretion and expression, mainly through the NF-κB signaling pathway (49). In the present study, we confirmed that hispolon can inhibit the migration of MCF-7, breast cancer cells by a completely different mechanism.…”
Section: Discussionsupporting
confidence: 74%
“…MMPs, the family of Zn-dependent endopeptidases, are associated with the invasive properties of metastatic cancer cells (28,29). It has been reported that MMP9 is overexpressed in breast cancer cells and is correlated with the invasion and metastasis of breast cancer (30,31). Given that SENP1 affected the cancer invasion and metastasis, we further investigated whether the expression of MMP9 could be controlled by SENP1.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB can activate a great number of genes involved in stress responses, inflammation, apoptosis and autophagy. NF-κB subunit 1 (P50) homodimers, or P50/P65 or P50/c-Rel heterodimers, bind to the NF-κB DNA-binding sites in the promoter regions of numerous stress-response genes, suggesting a complex regulation network at gene and physiological levels, controlled by NF-κB in stress response ( 41 ). Accumulated evidence indicates that the transcription factor NF-κB is critical for cellular protection against a variety of genotoxic agents, including irradiation, and that the inhibition of NF-κB may result in radiosensitization in radioresistant cancer cells ( 42 ).…”
Section: Discussionmentioning
confidence: 99%